Specific receptors and imaging reagents for certain heavy metal toxins - Anila, H. A.; Ali, F.; Das, A. (Comprehensive supramolecular chemistry II, 2017)
Among various elements, mercury (Hg) and palladium (Pd) are featured in all lists of heavy metal toxins. Mercury is xenobiotics and toxic even at trace levels of exposure either in elemental (if aerosolized) or in its two ionic forms (viz. Hg(I) and Hg(II)). Importantly, the most common oxidation state of mercury is Hg(II) and this has an appreciably high value for enthalpy of solvation in aqueous media. This fact along with a high spin-orbit coupling constant value are not conducive for designing efficient luminescence ON-based receptors for Hg(II), which are essential for either detection or imaging of such toxins inside the cells or in specific organs. Such sensors have significance in evaluating the influence of such toxins in human physiology as well as in clinical diagnostics. Analogously, Palladium (in oxidation states of 0, II, and IV) is commonly used as a catalyst for the synthesis of various drugs or active pharmaceutical intermediates. Despite best efforts in purification and elimination of palladium used in such reactions, residual concentrations of Pd are often higher than the permissible level set by the World Health Organization. The affinity of Pd toward thiol-containing amino acids, proteins, DNA, or other macromolecules is known to cause physiological disorders. All these necessitate the design and development of efficient imaging reagents that are specific toward a certain cationic analytes and allow for the real-time monitoring for assessing the adverse influences on human physiology. Recent advances in such reagents primarily for Hg(II), Pd(0), and Pd(II) are discussed.